D Dukungan Sosial Dengan Tingkat Stress Orang Tua Yang Memiliki Anak Penyandang Disabilitas di Klinik Pelangi Centre Development Neurorehabilitation Ponorogo - Filia Icha Sukamto; Imaniar Dwi Alda; Metti Verawati (LPPM Universitas Sari Mulia, 2022)
Background: Parents who have children with disabilities will make parents think what happened to their children that causes feelings of stress. Therefore, it is necessary to have social support from family, friends and even the community. Good social support will affect stress levels. Objective: The purpose of this study was to determine the relationship between social support and the stress level of parents who have children with disabilities at the Pelangi Clinic, Center for Neurorehabilitation Development, Ponorogo. Method: The design of this study was cross sectional. The population in this study were parents who had children with disabilities as many as 100 respondents. The sample in this study were 100 respondents. Collecting data using a questionnaire with Chi-Square analysis test. Result: The results of this study indicate that from 100 respondents, using the Total Sampling technique. 57 respondents (57.0%) received good social support, and 43 respondents (43%). Stress levels for parents at the Pelangi Clinic Center for Neurorehabilitation Development Ponorogo said 53 respondents (53%) with moderate stress levels, 28 respondents (28%) with mild stress levels and 19 respondents (19%) with severe stress levels. The results of the Chi-Square statistic test showed that p value = 0.000 < (0.05) so that H0 was rejected, which means that there is a relationship between social support and the stress level of parents who have children with disabilities at the Pelangi Clinic Center for Neurorehabilitation Development, Ponorogo. Conclusion: Social support from friends, family and even the community greatly affects the stress level of parents of children with disabilities. Information support, instrumental support, emotional support, appreciation support are needed by parents to reduce the risk of stress.